Evaluating the Risk of Suicide and Violence in Severe Mental Illness: A Feasibility Study of Two Risk Assessment Tools (OxMIS and OxMIV) in General Psychiatric Settings - Beaudry, Gabrielle; Canal-Rivero, Manuel; Ou, Jianjun; Matharu, Jaskiran; Fazel, Seena; Yu, Rongqin (Frontiers in Psychiatry, 2022)
Two OxRisk risk assessment tools, OxMIS and OxMIV, were developed and validated using national linked registries in Sweden, to assess suicide and violence risk in individuals with severe mental illness (schizophrenia-spectrum disorders and bipolar disorders). In this study, we aim to examine the feasibility and acceptability of the tools in three different clinical services. We employed a two-step mixed-methods approach, by combining quantitative analyses of risk scores of 147 individual patients, and thematic analyses of qualitative data. First, 38 clinicians were asked to use OxMIS and OxMIV when conducting their routine risk assessments in patients with severe mental illness. The risk scores for each patient were then compared to the unstructured clinical risk assessment made by the treating clinician. Second, we carried out semi-structured interviews with the clinicians on the acceptability and utility of the tools. Thematic analysis was conducted on the qualitative data to identify common themes, in terms of the utility, accuracy, and acceptability of the tools. The investigations were undertaken in three general adult psychiatric clinics located in the cities of Barcelona and Sevilla (Spain), and Changsha (China). More than 90% of included patients were in low-risk categories for violence based on a pre-specified threshold. In contrast, most patients (83.6%) were found to be at increased risk for suicide (based on a 0.5% cut-off). In the thematic analysis, clinicians described the tools as easy to use, and also found that the risk score improved risk management. Potential additions to predictors were suggested, including family history and the patient’s support network. Concordance rates of risk estimates between the tools and clinicians was high for violence (94.4%; 68/72) and moderate for suicide (50.0%; 36/72). We found a significant correlation between the unstructured clinical risk estimated by clinicians and those for OxMIS in a subsample, r(58)=.51, p<.001. Both OxMIS and OxMIV are feasible and practical in different general adult psychiatric settings. Clinicians interviewed found that both tools provide a useful structured approach to estimate the risk of suicide and violence. Risk scores from OxMIS and OxMIV can also be used to assist clinical decision-making for future management.